Involvement of POMC neurons in LEAP2 regulation of food intake and body weight - Chu, Guangpin; Peng, Hualing; Yu, Nana; Zhang, Yuejin; Lin, Xueling; Lu, Yisheng (Frontiers in Endocrinology, 2022)
Liver-expressed antimicrobial peptide 2 (LEAP2) is a newly discovered antagonist of the growth hormone secretagogue receptor (GHSR) and is considered the first endogenous peptide that can antagonize the metabolic actions of ghrelin. The effects of ghrelin administration on feeding behavior, body weight, and energy metabolism involve the activation of orexigenic neurons in the hypothalamus arcuate nucleus (ARC). It is unclear, however, if LEAP2 applied directly to the hypothalamus ARC affects these metabolic processes. Here, we show that overexpression of LEAP2 in the ARC through adeno-associated virus (AAV) reduced food intake and body weight in wild-type (WT) mice fed chow and a high-fat diet (HFD) and improved metabolic disorders. LEAP2 overexpression in the ARC overrides both central and peripheral ghrelin action on chow diet. Interestingly, this AAV-LEAP2 treatment increased proopiomelanocortin (POMC) expression while agouti-related peptide (AGRP)/neuropeptide Y (NPY) and GHSR levels remained unchanged in the hypothalamus. Additionally, intracerebroventricular (i.c.v.) administration of LEAP2 decreased food intake, increased POMC neuronal activity, and repeated LEAP2 administration to mice induced body weight loss. Using chemogenetic manipulations, we found that inhibition of POMC neurons abolished the anorexigenic effect of LEAP2. These results demonstrate that central delivery of LEAP2 leads to appetite-suppressing and body weight reduction, which might require activation of POMC neurons in the ARC.